Evaluating aerosol and splatter following dental procedures: Addressing new challenges for oral health care and rehabilitation. (8th October 2020) - Allison, James R.; Currie, Charlotte C.; Edwards, David C.; Bowes, Charlotte; Coulter, Jamie; Pickering, Kimberley; Kozhevnikova, Ekaterina; Durham, Justin; Nile, Christopher J.; Jakubovics, Nicholas; Rostami, Nadia; Holliday, Richard
Abstract: Background: Dental procedures often produce aerosol and splatter which have the potential to transmit pathogens such as SARS‐CoV‐2. The existing literature is limited. Objective(s): To develop a robust, reliable and valid methodology to evaluate distribution and persistence of dental aerosol and splatter, including the evaluation of clinical procedures. Methods: Fluorescein was introduced into the irrigation reservoirs of a high‐speed air‐turbine, ultrasonic scaler and 3‐in‐1 spray, and procedures were performed on a mannequin in triplicate. Filter papers were placed in the immediate environment. The impact of dental suction and assistant presence were also evaluated. Samples were analysed using photographic image analysis and spectrofluorometric analysis. Descriptive statistics were calculated and Pearson's correlation for comparison of analytic methods. Results: All procedures were aerosol and splatter generating. Contamination was highest closest to the source, remaining high to 1‐1.5 m. Contamination was detectable at the maximum distance measured (4 m) for high‐speed air‐turbine with maximum relative fluorescence units (RFU) being: 46, 091 at 0.5 m, 3, 541 at 1.0 m and 1, 695 at 4 m. There was uneven spatial distribution with highest levels of contamination opposite the operator. Very low levels of contamination (≤0.1% of original) were detected at 30 and 60 minutes post‐procedure. Suction reduced contamination by 67‐75% at 0.5‐1.5 m. Mannequin and operator were heavily contaminated. The two analytic methods showed good correlation ( r  = 0.930, n = 244, P  < .001). Conclusion: Dental procedures have potential to deposit aerosol and splatter at some distance from the source, being effectively cleared by 30 minutes in our setting.